2014
DOI: 10.1007/s10753-014-9973-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants of Interleukin 17A Are Functionally Associated with Increased Risk of Age-Related Macular Degeneration

Abstract: Age-related macular degeneration (AMD) is the leading cause of irreversible blindness in elderly populations worldwide. Inflammation, among many factors, has been suggested to play an important role in AMD pathogenesis. Interleukin 17 (IL-17) is a proinflammatory cytokine that has been implicated in the pathogenesis of various autoimmune diseases. In the current study, we examined two single nucleotide polymorphisms (SNPs), rs2275913G/A and rs3748067C/T, in the IL-17A gene between AMD patients and healthy cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 24 publications
0
13
1
1
Order By: Relevance
“…reported that complement component C5a is increased in the circulation of AMD patients and that it promotes expression of the Th17 cytokines IL-17 and IL-22 by human CD4 + T-cells 41 . Also, an association between two single nucleotide polymorphisms in the IL-17 gene, rs2275913G/A and rs3748067C/T and AMD was reported 42 . IL-17 and TNF-α have been observed at higher concentrations in AMD patients and may be linked to a more favorable response to anti-VEGF therapy 43 .…”
Section: Discussionmentioning
confidence: 95%
“…reported that complement component C5a is increased in the circulation of AMD patients and that it promotes expression of the Th17 cytokines IL-17 and IL-22 by human CD4 + T-cells 41 . Also, an association between two single nucleotide polymorphisms in the IL-17 gene, rs2275913G/A and rs3748067C/T and AMD was reported 42 . IL-17 and TNF-α have been observed at higher concentrations in AMD patients and may be linked to a more favorable response to anti-VEGF therapy 43 .…”
Section: Discussionmentioning
confidence: 95%
“…49 Two SNPs within the IL-17A gene were recently reported to be associated with AMD as well as higher levels of IL-17A secretion from PBMC stimulated ex vivo . 62 Elevated IL-17A and IL-17RC levels were also detected in AMD lesions compared with normal macular tissues. 51 In vitro, IL-22 induced apoptosis of primary human RPE cells, 63 and IL-17A was shown to enhance production of inflammatory cytokines, including IL-6, IL-8 and CCL2, from ARPE-19 cells 64 as well as induce angiogenesis in human choroidal endothelial cells.…”
Section: Inflammatory Cytokines In Amdmentioning
confidence: 98%
“…An increase of IL-17 immunopositivity has been reported in GA eyes compared to control subjects, but IL-17-producing cells could not be identified [27]. Furthermore, genetic variants of IL-17 have been shown to be associated with AMD [28], while the reported association of hypomethylation of the IL-17 receptor [27] was not reproducible in another study [29]. …”
Section: Introductionmentioning
confidence: 99%